Inactivation influences the extent of inhibition of voltage-gated Ca+2 channels by Gem—implications for channelopathies - Allam, Salma; Levenson-Palmer, Rose; Chia Chang, Zuleen; Kaur, Sukhjinder; Cernuda, Bryan; Raman, Ananya; Booth, Audrey; Dobbins, Scott; Suppa, Gabrielle; Yang, Jian; Buraei, Zafir (Frontiers in Physiology, 2023)
Voltage-gated Ca2+ channels (VGCC) directly control muscle contraction and neurotransmitter release, and slower processes such as cell differentiation, migration, and death. They are potently inhibited by RGK GTP-ases (Rem, Rem2, Rad, and Gem/Kir), which decrease Ca2+ channel membrane expression, as well as directly inhibit membrane-resident channels. The mechanisms of membrane-resident channel inhibition are difficult to study because RGK-overexpression causes complete or near complete channel inhibition. Using titrated levels of Gem expression in Xenopus oocytes to inhibit WT P/Q-type calcium channels by ∼50%, we show that inhibition is dependent on channel inactivation. Interestingly, fast-inactivating channels, including Familial Hemiplegic Migraine mutants, are more potently inhibited than WT channels, while slow-inactivating channels, such as those expressed with the Cavβ2a auxiliary subunit, are spared. We found similar results in L-type channels, and, remarkably, Timothy Syndrome mutant channels were insensitive to Gem inhibition. Further results suggest that RGKs slow channel recovery from inactivation and further implicate RGKs as likely modulating factors in channelopathies.